Ökonomische Folgen: Was Kriege die Welt kosten - Jonathan-Julian Federle; André Meier; Gernot J. Müller; Willi Mutschler; Moritz Schularick (Wirtschaftsdienst, 2024)
– Amid escalating geopolitical tensions, we offers insights into the far-reaching consequences of wars. Based on a new dataset on major conflicts since 1870, the findings show that wars cause a substantial decline in GDP and spike in inflation within war zones. Interestingly, countries geographically close to war zones experience significant economic disruptions, even when neutral to the conflict, whereas countries far from the conflict may see minimal to slightly positive spillovers. The study demonstrates how wars represent a massive negative supply shock, with geographical proximity and trade integration explaining the varying effects on different countries.
Keywords: E50; F40; F50; 330; Krieg; Kriegsfolgen; Wirtschaftslage; Welt; Krieg; Kriegsfolgen; Wirtschaftslage; Welt